Development of a thermal control coating optimized for cryogenic space applications. Issue 1 (1st May 2022) - Krenn, A; Youngquist, R; Gibson, T; Snyder, S
Abstract: As NASA endeavors to extend the human presence in space beyond low Earth orbit, methods to efficiently store cryogenic propellants in space are required. Current state of the art rigid thermal control coatings absorb approximate 6% of the total solar irradiance, while state of the art thermal control paints absorb approximately 10% of the total solar irradiance. Consequently, radiative heat transfer a lone makes passive storage of cryogens in space impossible. A new rigid thermal control coating is in development and has achieved solar absorption values as low as -0.6 % (compared to a NIST standard) while maintaining high emissivity. This negative value for a rigid tile of pure yttria has required a new testing method be developed. Rigid tiles are very high performance but have more mass than paints and paper-th in coatings. Tiles must have a metallic substrate and create application challenges. While some use cases may necessarily address the challenges associated with rigid tiles in order to achieve required performance, a similar paint-like coating was also developed. The spray-on version of the new thermal control coating is easily applied to large complex surfaces and is very low mass. This version is also primarily yttria but includes a potassium bromide binder. Application to various substrates shows solar absorption values consistently below 5%, with a minimum of 2.8% achieved. Details of each version of this coating, along with test data is discussed.